Sirqah In The Concept Of Islamic Criminal Law: Theft That Is Not Restricted (Hudud Sanctions) - Suhardiman; Mhd Yadi Harahap (ISNU Sumatera Utara, 2025)
Theft is one of the criminal acts that receives special attention in Islamic criminal law. This act is categorized as sirqah and has hudud sanctions if it meets certain requirements, such as the minimum amount of property, legal evidence, and the condition of the perpetrator who is mature and sane in his mind. The phenomenon of theft that does not meet hudud requirements creates complexity in law enforcement, because it still harms the victim but cannot be subject to a fixed punishment. This study highlights the relevance of the ta'zir mechanism as a flexible and humanistic alternative sanction, as well as the role of Islamic legal norms in balancing legal certainty, social justice, and rehabilitation of perpetrators. This study aims to analyze the concept of sirqah in Islamic criminal law, evaluate the application of hudud and ta'zir sanctions, and examine the relevance of Islamic legal norms in the context of unrestricted theft. The normative approach is used by examining primary legal sources such as the Qur'an, Hadith, and fiqh books, as well as secondary literature in the form of journals, books, and academic documents. The analysis was carried out qualitative-descriptive to understand the legal mechanism, the principles of maqashid al-shari'ah, and the flexibility of ta'zir sanctions. The results of the study show that non-hudud theft is still regulated through ta'zir sanctions that are adjusted to the intention, condition of the perpetrator, and social impact. Islamic legal norms emphasize the protection of victims' rights, the certainty of court procedures, and the rehabilitative effect for perpetrators. Ta'zir is an adaptive instrument to uphold justice, educate the community, and prevent the repetition of criminal acts. This approach shows that Islamic criminal law is not only repressive, but also humanistic, preventive, and restorative. The conclusion of this study confirms that Islamic criminal law is able to balance legal certainty, social justice, and rehabilitation goals in dealing with non-hudud theft. The normative and procedural application of ta'zir ensures the protection of victims' rights while providing educational and moral opportunities for perpetrators, so that the law remains relevant and adaptive to modern socio-economic dynamics.